"Increasing Crop Yield through Advanced Irrigation Technologies: World and Uzbekistan Experiences" - Rustamjon ogli, Nasibov Boburbek; Karimovich, Jo’rayev Shohjahon; Odilovich, Khomidov Avaz (American Journal of Biodiversity, 2025)
Chickpea (Cicer arietinum L.) is an important leguminous crop worldwide, especially in semi-arid regions. Efficient irrigation is crucial to maximize its yield and ensure food security. This article explores the advantages of modern irrigation technologies for chickpea cultivation, particularly drip irrigation. We discuss chickpea planting practices, phenological stages, various irrigation methods, and the benefits of drip irrigation in chickpea production. Furthermore, we synthesize global research findings with specific studies conducted in Uzbekistan, demonstrating the impact of improved irrigation on chickpea yield and water use efficiency. The discussion highlights the potential of these technologies to enhance productivity and contribute to sustainable agriculture.